The “Neglected Viruses” of Taihu: Abundant Transcripts for Viruses Infecting Eukaryotes and Their Potential Role in Phytoplankton Succession - Pound, Helena L.; Gann, Eric R.; Tang, Xiangming; Krausfeldt, Lauren E.; Huff, Matthew; Staton, Margaret E.; Talmy, David; Wilhelm, Steven W. (Frontiers in Microbiology, 2020)
Drivers of algal bloom dynamics remain poorly understood, but viruses have been implicated as important players. Research addressing bloom dynamics has generally been restricted to the virus-infection of the numerically dominant (i.e., bloom forming) taxa. Yet this approach neglects a broad diversity of viral groups, limiting our knowledge of viral interactions and constraints within these systems. We examined hallmark virus marker genes in metatranscriptomic libraries from a seasonal and spatial survey of a Microcystis aeruginosa bloom in Lake Tai (Taihu) China to identify active infections by nucleocytoplasmic large DNA viruses (NCLDVs), RNA viruses, ssDNA viruses, bacteriophage, and virophage. Phylogenetic analyses revealed a diverse virus population with seasonal and spatial variability. We observed disproportionately high expression of markers associated with NCLDVs and ssRNA viruses (consistent with viruses that infect photosynthetic protists) relative to bacteriophage infecting heterotrophic bacteria or cyanobacteria during the height of the Microcystis bloom event. Under a modified kill-the-winner scheme, we hypothesize viruses infecting protists help suppress the photosynthetic eukaryotic community and allow for the proliferation of cyanobacteria such as Microcystis. Our observations provide a foundation for a little considered factor promoting algal blooms.